Optimasi Pengolahan Tomat Untuk Pencegahan Kanker Serviks Di Perumahan Jember Permai I Kecamatan Sumbersari Kabupaten Jember - Cindera Rosa Damascena; Nur Halimah; Ines Ratni Parvitasari (Institut Nalanda, 2023)
Cancer is one of the diseases that cause significant deaths. Cancer is most commonly suffered by women classified as breast cancer and cervical cancer. Breast cancer is the highest cause of death for female cancer sufferers in Indonesia. One alternative that can be done to prevent or inhibit cancer is the use of chemopreventive agents that can be found by exploring natural materials. Chemopreventive agents can be found in fruits and vegetables, which contain lots of lycopene. The most significant source of lycopene can be obtained from tomatoes. Tomatoes are known to be relatively cheap and easy to process, and they are always available in all seasons. Therefore, tomato processing can be used as a chemopreventive effort that all groups can carry out. Processing tomatoes can be used as an alternative prevention and effort to inhibit the growth of cancer cells for ordinary people by participating in training, mentoring and consultation activities.